2012
DOI: 10.1007/s13744-012-0083-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Boll Weevil Anthonomus grandis Boheman (Coleoptera: Curculionidae) Suppression Program in the State of Goiás, Brazil

Abstract: The boll weevil Anthonomus grandis Boheman (Coleoptera: Curculionidae) is the most important cotton pest in Brazil. A large-scale field-testing of a Boll Weevil Suppression Program (BWSP) was implemented to assess its technical and operational feasibility for boll weevil suppression in the state of Goiás, Brazil. The pilot plan focused on 3,608 ha of cotton during the 2006/2007 and 6,011 ha in the 2007/2008 growing seasons; the areas were divided into four inner zones with an outer buffer zone. We analyzed dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 9 publications
1
12
0
2
Order By: Relevance
“…At the end of the crop cycle, the adults search for alternative food sources and shelter in order to survive the fallow period. This mass egress, both during and after the harvesting procedures, has been reported in the state of São Paulo, in the Distrito Federal, and in the state of Bahia by Campanhola et al (1988), Ribeiro et al (2010), and Macêdo et al (2015), respectively, and has been confirmed in monitoring studies using traps baited with pheromone, carried out in cotton-producing areas in the state of Goiás (Lima Jr. et al, 2013).…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…At the end of the crop cycle, the adults search for alternative food sources and shelter in order to survive the fallow period. This mass egress, both during and after the harvesting procedures, has been reported in the state of São Paulo, in the Distrito Federal, and in the state of Bahia by Campanhola et al (1988), Ribeiro et al (2010), and Macêdo et al (2015), respectively, and has been confirmed in monitoring studies using traps baited with pheromone, carried out in cotton-producing areas in the state of Goiás (Lima Jr. et al, 2013).…”
Section: Resultssupporting
confidence: 72%
“…This may explain the high number of adults captured in the traps, as noted at the end of the cotton cycle (Showler, 2003;Lima Jr. et al, 2013).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The Cotton boll weevil ( Anthonomus grandis ) is an economically important crop insect pest that attacks cotton fields, particularly in South America (de Lima et al, 2013). The larvae live and feed off the cotton flowers and buds, causing serious damage to cotton yields.…”
Section: Introductionmentioning
confidence: 99%
“…Boll weevil immature stages exhibit low natural mortality from natural enemies [ 9 , 10 ] and are difficult to control with insecticides, because they are partially protected inside cotton fruit bodies. Current insecticide-based practices require 5–6× sequential sprays at ~5-day intervals, with the intent of killing adults emerging from fallen fruiting bodies before they are able to oviposit [ 11 ]. Technologies such as transgenic cotton also have no impact on boll weevils [ 12 ].…”
Section: Introductionmentioning
confidence: 99%